Generation of actionable, cancer-specific neoantigens from KRAS(G12C) with adagrasib - Lorenzo Maso; Epsa Rajak; Takamitsu Hattori; Zhengshan Hu; Akiko Koide; Benjamin G. Neel; Shohei Koide (Proceedings of the National Academy of Sciences, 2025)
Effective immune therapy against cancer ideally should target a cancer-specific antigen, an antigen that is present exclusively in cancer cells. However, there is a paucity of cancer-specific antigens that are endogenously produced. HapImmune™ technology utilizes covalent inhibitors directed to an intracellular cancer driver to create cancer-specific neoantigens in the form of drug–peptide conjugates presented by class I MHC molecules. Our previous study with sotorasib, an FDA-approved covalent inhibitor of KRAS(G12C), demonstrated that drug-treated cells produce such neoantigens and can be killed by T cell engagers directed against the drug–peptide/MHC complex. Thus, this technology can unite targeted and immune therapies. In the present study, we examined whether this approach could generalize to another FDA-approved KRAS(G12C) inhibitor, adagrasib, whose chemical structure and cysteine reactivity differ substantially from sotorasib. We developed antibodies selective to adagrasib-KRAS(G12C) peptides presented by HLA-A*03 and A*11 that also show cross-reactivity to other KRAS(G12C) inhibitors presented in the same manner. Cryoelectron microscopy structures revealed a mode of adagrasib-peptide/HLA recognition distinctly different from that of sotorasib-directed HapImmune antibodies. The antibodies in a bispecific T cell engager format killed adagrasib-resistant lung cancer cells upon adagrasib treatment. These results support the broad applicability of the HapImmune approach for creating actionable cancer-specific neoantigens and offer candidates for therapeutic development.